1987
DOI: 10.2307/1590894
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Avian Urolithiasis on a Large Commercial Egg Farm

Abstract: A significant outbreak of avian urolithiasis was observed on a large commercial egg farm. From the initial outbreak site (a single laying house), the incidence of urolithiasis slowly spread in the ensuing months to numerous other laying houses. Increasing mortality associated with urolithiasis commenced during late growout to early lay and then leveled off when egg production peaked. At the height of the outbreak, mortality was typically 0.5% per week; 75% of this mortality was due to urolithiasis. The clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 15 publications
0
8
1
Order By: Relevance
“…Egg production was affected during this outbreak; the egg drop was estimated to 12%. This result doesn't correlate to the observations of (Cowen et al, 1986) who reported that layers affected by urolithiasis remain productive.…”
Section: Necropsy Observationscontrasting
confidence: 99%
See 2 more Smart Citations
“…Egg production was affected during this outbreak; the egg drop was estimated to 12%. This result doesn't correlate to the observations of (Cowen et al, 1986) who reported that layers affected by urolithiasis remain productive.…”
Section: Necropsy Observationscontrasting
confidence: 99%
“…Despite some differences in the age of the affected birds, necropsy observations and case history of this urolithiasis outbreak were similar to urolithiasis in caged layers described in United States (Brown et al, 1987;Cowen et al, 1986, Mallinson et al, 1984. Authors investigated the pathology of same urolithiasis outbreak in caged layers.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Urolithiasis sporadically causes mortality that is characterised by visceral gout, obstructive urolith (kidney stone) formation, and atrophy of mineralised or obstructed kidney tissue accompanied by compensatory hypertrophy of undamaged kidney tissue (Randall et ai, 1977;Jones et al, 1978;Blaxland et al, 1980;Siller, 1981;Wideman et al, 1983;Mallinson et al, 1984;Cowen et al, 1987a;Brown et al, 1987). Studies based on original observations (Shane et al, 1969) confirmed that urolithiasis can be induced when immature pullets are fed on diets containing more than 30 g/kg calcium and less than 4-5 g/kg available phosphorus Niznik et al, 1985;Wideman and Cowen, 1987;Glahn et al, 1988aGlahn et al, ,b, 1989.…”
Section: Introductionmentioning
confidence: 99%
“…Affected birds may die of kidney failure, exhibiting symptoms that include visceral gout, focal mineralization of the kidneys, degeneration of portions of kidneys "upstream" from kidney stones obstructing the ureter, and compensatory hypertrophy by undamaged kidney tissue (Randall et ah, 1977;Jones et al, 1978;Blaxland et al, 1980;Siller, 1981;Wideman et al, 1983;Mallinson et al, 1984;Brown et al, 1987;Cowen et al, 1987b). Urolithiasis can be induced by feeding 4-to 8-wk-old pullets diets containing in excess of 3% Ca and less than .45% available P (aP) (Shane et al, 1969;Niznik et al, 1985;Wideman et al, 1245Wideman et al, 1985Wideman and Cowen, 1987;Glahn et al, 1988aGlahn et al, ,b, 1989.…”
Section: Introductionmentioning
confidence: 99%